PERANCANGAN SISTEM PERPARKIRAN DENGAN METODE FIFO (FIRST IN FIRST OUT) - Rio Elpranata Tarigan; Pilipus Tarigan (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2019)
Queue is an ordinary event in everyday life and other situations are events that are often encountered. In the case of queuing, time is a component that is very important and valuable, therefore as far as possible the existing system can reduce excessive use of time so as to achieve effectiveness and efficiency in terms of the use of this time, the public or visitors who are usually queued to be part of a process in service. The distribution of anthrin organized by several jambur to help the community or visitors in terms of service in the process of obtaining something. Jambur Tamsaka is one of the jambur which gives the best queue servants to the public or visitors for discipline and time management for their visitors. In accordance with the rules determined by Jambur Tamsaka to obtain a queue block, then visitors have krteria in getting the blocks and queuing process. From this basis created a system to determine the recipient in the queue process, and the methods used in the system